Pengembangan Bahan Ajar Dengan Rangkaian LEAD (LISTEN, EXPLORE, ANALYZE, AND DO) Mata Pelajaran Prakarya dan Kewirausahaan Berbasis Potensi Lokal Pulau Bawean Kabupaten Gresik Berbantu Google Classroom - Himmatusy Syarifah; Harwanto; Retno Danu Rusmawati (Jurnal Penelitian Pendidikan IPA, 2023)
Researchers are developing teaching materials based on the problems identified in this area. There is still a lack of teaching materials that integrate social values ​​based on local wisdom. The objectives of the research to develop these teaching materials are: Development of craft and entrepreneurship educational materials, learning the feasibility of craft and entrepreneurship educational materials by material and design experts, effectiveness of craft and entrepreneurship educational materials for MTS Umar Masud students at IX Know your gender. Lessons were developed based on the opinions of teachers and students. Through the research and development (R&D) of his LEAD (Listen, Explore, Analyze, Do) series powered by Google Classroom, the researcher develops craft and entrepreneurship teaching materials based on local wisdom, Combining craft and entrepreneurship. Validation sheet average scores obtained by three experts (materials, subject matter, instructional design) were 86% for content or material feasibility, 96% for presentation feasibility, simple usability and practicality was 89% for gender. The average value of the product attractiveness test results of students' answers is 84%, indicating that students' answers are highly interested in using craft materials and starting businesses that emphasize the potential of the region. As a result of the analysis, it was found that the effectiveness of teaching materials for crafts and entrepreneurship that make use of the potential of the region is included in effectively.